2017
DOI: 10.3346/jkms.2017.32.7.1139
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriAntigens Inducing Early Immune Response in Infants

Abstract: To identify the Helicobacter pylori antigens operating during early infection in sera from infected infants using proteomics and immunoblot analysis. Two-dimensional (2D) large and small gel electrophoresis was performed using H. pylori strain 51. We performed 2D immunoglobulin G (IgG), immunoglobulin A (IgA), and immunoglobulin M (IgM) antibody immunoblotting using small gels on sera collected at the Gyeongsang National University Hospital from 4–11-month-old infants confirmed with H. pylori infection by pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…15,29) Thirty-three H. pylori isolates obtained from 11 members of three families showed familial clustering of identical random amplified polymorphic DNA fingerprinting types, which might be supportive evidence of person-to-person transmission among closely related individuals such as family members. 6,33) Many epidemiologic studies involving children showed that H. pylori infection occurred in early childhood and that the infection rate increased at around 5-7 years of age. 2,28) During these ages, children usually start to experience group life, for example, kindergarten or elementary school, which may support the possibility of person-to-person transmission.…”
Section: Prevalence Of H Pylori Infection During Childhood and Adolementioning
confidence: 99%
See 1 more Smart Citation
“…15,29) Thirty-three H. pylori isolates obtained from 11 members of three families showed familial clustering of identical random amplified polymorphic DNA fingerprinting types, which might be supportive evidence of person-to-person transmission among closely related individuals such as family members. 6,33) Many epidemiologic studies involving children showed that H. pylori infection occurred in early childhood and that the infection rate increased at around 5-7 years of age. 2,28) During these ages, children usually start to experience group life, for example, kindergarten or elementary school, which may support the possibility of person-to-person transmission.…”
Section: Prevalence Of H Pylori Infection During Childhood and Adolementioning
confidence: 99%
“…3) H. pylori infection may occur in infancy or early childhood and generally persists for life if left untreated. 2,[4][5][6] Chronic H. pylori infection plays a pivotal role in the development of peptic ulcer, atrophic gastritis, and gastric cancer. 7) The H. pylori infection status in children versus adults is not fully known since most infected children remain asymptomatic and studies are limited.…”
Section: Introductionmentioning
confidence: 99%
“… 24 H. pylori strain 51 was isolated from a patient with duodenal ulcer at GNUH in 1988 and has been studied extensively since then. 14 15 18 22 24 25 26 27 Briefly, H. pylori strain 51 was cultured for 18 hours under the environment of 37°C, 5%–10% CO 2 and 100% humidity on Mueller-Hinton agar supplemented with 10% bovine serum. Bacterial cells from each plate were harvested and pelleted by centrifugation at 4,000 × g for 15 minutes.…”
Section: Methodsmentioning
confidence: 99%
“… 11 12 13 14 15 H. pylori infection can take hold during infancy or early childhood and colonization generally persists for life if left untreated. 16 17 18 …”
Section: Introductionmentioning
confidence: 99%
“…H. pylori flagellin is an important virulent factor in the pathogenesis of gastric mucosal and is considered as one of the most important stimulators of the immune system and acts as a ligand for toll-like receptor 5 (TLR5) of the host cells (YAN et al, 2003;SADEGHI and DOOSTI, 2017). FlaA protein is the predominant subtype and reduces TLR5 internal activity in this pathogen so it might help the bacterium to escape from the host immune response and causes continuous bacterial colonization (SADEGHI and DOOSTI, 2017;SEO et al, 2017).…”
mentioning
confidence: 99%